When the Subject is the Object: Islamic Advice Literature Modes and the Treatment of Slavery in The Qābūs Nāmih and The Nasirean Ethics. Issue 3 (3rd May 2016) - Sadr, Amin Azad
Abstract : This paper investigates the difference of perspective which informs The Qābūs Nāmih's and The Nasirean Ethics' respective treatments of the topic of slavery. While in various parts of their discussions both works show an engagement with each side of the hybrid status of a slave's existence as both subject and object, The Qābūs Nāmih deals with the issue almost entirely in terms of the slave's status as an object, while The Nasirean Ethics engages this issue with clear acknowledgments to his/her status as a subject. It is possible that the divergent approaches of these two works are a reflection of the two distinct modes of the genre of Islamic advice literature in which they were respectively written.